Implementation of Early Breastfeeding Initiation Challenges After Sectio Caesarea in Hospital - Puji Lestari; Sri Achadi Nugraheni; Ayun Sriatmi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Behavior of early initiation of breastfeeding in postpartum mothers is still a health problem in the world. Early initiation of breastfeeding has become an internationally and nationally recommended program as part of Mother and Baby Friendly Hospital services. Caesarean section is one of the obstacles in implementing early initiation of breastfeeding. This scoping review aims to assess the policy of early breastfeeding initiation after cesarean section in hospitals. This research design is a scoping review, using 4 databases, namely Google Scholar, Ebsco, Pro Quest, and Science Direct. The stages and flow of selecting research articles using PRISMA (Preferred Reporting Items For Systematic reviews and Meta-Analyses) Flowchart, and to assess the quality of the article researchers used a checklist from the Joanna Briggs Institute. Literature study that summarizes several accredited journal articles from 2018-2023 that are relevant to the title. This research selected quantitative and qualitative research articles with cross-sectional or case control research designs. In the journal search, researchers used boolean operators for predetermined keywords, adding "OR", "AND" according to the topic. The results found two themes and six subthemes from the 8 articles screened, namely the success factors of breastfeeding in post-cesarean section mothers, maternal knowledge, maternal attitudes, decisions in planning labor and implementation of early breastfeeding initiation. Meanwhile, efforts to make early breastfeeding initiation a success continue with the support of health workers and program policies. Support and policy efforts from health care providers have a positive influence on breastfeeding mothers, especially mothers who undergo cesarean delivery in hospitals. Keywords: Challenges, Early initiation of breastfeeding, Hospital, Post sectio caesarea